ChemInform Abstract: Titanium and Zirconium Hydride‐Catalyzed Regioselective Isomerization of 1, 4‐Dihydrofulvenes: Access to 1‐Substituted 1, 2‐Dihydrofulvenes. Issue 18 (April 2016) - Joseph, Jomy; Preethalayam, Preethanuj; Radhakrishnan, K. V.; Jaroschik, Florian; Vasse, Jean‐Luc
Abstract: The Zr‐catalyzed double‐bond migration in 1, 4‐dihydrofulvenes (VI) and (VIII), obtained by Zr‐catalyzed hydroalumination of pentafulvene (I) and a subsequent addition of aldehyde at low temperature, give rises to isomeric 1, 2‐dihydrofulvenes (III) and (IX).